Intervensi dinas perindustrian perdagangan koperasi dan ukm kota Tidore kepulauan terhadap pengembangan kapasitas kelompok pengrajin gerabah di desa Maregam - Umasugi, Mohbir (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
In terms of human resource training, use of technology, capital, and access to marketing, there is no legal umbrella or regional regulation that forms the basis for government policies in the industrial sector. The data analysis method used in this research is descriptive qualitative. Qualitative descriptive is a method used to explore findings in the field. The results showed that in terms of human resource training there had been various trainings carried out, so the groups of pottery craftsmen already knew more or less about how to make decorative pottery. Judging from the use of technology, the results have not been maximized in carrying out the production process from changing traditional technology to new technology due to the habits of the pottery craftsman group who have been producing pottery in the traditional way. In terms of capital, there has been assistance from the Tidore Islands City Government for the pottery craftsman group in Maregam Village in stages, both in the form of capital loans and goods, and marketing access has not been maximized because marketing is only limited to the North Maluku area. It can be said that the authorities still have a fairly low concern for the pottery craftsmen in Mare Gam Village.